Evaluation of retraction time as a predictor of postoperative motor dysfunction after minimally invasive transpsoas interbody fusion at L4-L5. (March 2019) - Mueller, Kyle; McGowan, Jason; Kane, Stephen; Voyadzis, Jean-Marc
Abstract: Background: Complications associated with the lateral lumbar transpsoas approach largely comprise various nerve-related syndromes particularly at L4-5. Quadriceps weakness can occur from stretch injury to the femoral nerve during retraction. Objective: The purpose of this study is to evaluate the role of retraction time in the development of postoperative neuropathic motor weakness at the L4-5 level. Methods: A retrospective review of a prospectively collected database at a single institution was reviewed over a two-year period (March 2014–2016) for a single surgeon. Twenty-six patients undergoing single level LLIF at L4-5 were identified. Pre- and postoperative data collection obtained included motor function grading (0–5/5) with a minimum of 3-month postoperative follow-up. Intraoperative data collection included retraction time (RT) defined as the time the retraction system was affixed to the spine and expanded to the time of closure and removal. Two-Tailed T-Test was used to determine clinical significance. Results: 50% of patients had leg weakness after surgery (13/26). All postoperative motor deficits were at least antigravity strength (>3/5) and all deficits resolved. The mean RT for the motor dysfunction cohort was 29 min (14–51) compared to 27.5 min for the cohort without postoperative weakness (19–37) (p = 0.685). Conclusion: The results of this study suggest that longer retraction time (within a range of 14–51 min) did not correlate with a greater risk of postoperative neuropathic quadriceps muscle dysfunction for lateral lumbar interbody fusions performed at L4-5. Other factors may contribute to postoperative neurologic dysfunction regardless of RT. Motor deficits resolved quickly after surgery.